2016
DOI: 10.3389/fimmu.2016.00137
|View full text |Cite
|
Sign up to set email alerts
|

NETosing Neutrophils Activate Complement Both on Their Own NETs and Bacteria via Alternative and Non-alternative Pathways

Abstract: Neutrophils deposit antimicrobial proteins, such as myeloperoxidase and proteases on chromatin, which they release as neutrophil extracellular traps (NETs). Neutrophils also carry key components of the complement alternative pathway (AP) such as properdin or complement factor P (CFP), complement factor B (CFB), and C3. However, the contribution of these complement components and complement activation during NET formation in the presence and absence of bacteria is poorly understood. We studied complement activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 44 publications
6
104
0
4
Order By: Relevance
“…This is in agreement with recent reports of NETs (48, 49) and suggested that complement is regulated on the NETs to allow opsonization and phagocytosis to terminate the immune response. Clearance of extracellular traps is achieved with the help of DNase I, which cleaves the extracellular DNA and facilitates uptake and clearance of DNA by macrophages (28).…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with recent reports of NETs (48, 49) and suggested that complement is regulated on the NETs to allow opsonization and phagocytosis to terminate the immune response. Clearance of extracellular traps is achieved with the help of DNase I, which cleaves the extracellular DNA and facilitates uptake and clearance of DNA by macrophages (28).…”
Section: Discussionsupporting
confidence: 94%
“…However, tumor cells can secrete complement proteins that stimulate tumor growth and epithelial mesenchymal transition (47,48). Complement activation can also promote platelet-granulocyte aggregation, thrombosis, and NETosis (49,50). CR3 signaling was associated with suppression of NK cell function and increased growth of syngeneic melanoma (51).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils not only store C3 but also FP, the only complement regulator that enhances complement activation, which can be secreted upon stimulation [30,35,37]. Besides the release of C3 and FP, FB was also demonstrated to be secreted upon activation of neutrophils [38]. Locally released FP, FB and C3 could provide a local platform for further complement activation via the AP.…”
Section: Polymorphonuclear Leucocytesmentioning
confidence: 99%